Tumor Imaging: Colorectal Cancer Diagnosis Using Enzyme‐Sensitive Ratiometric Fluorescence Dye and Antibody–Quantum Dot Conjugates for Multiplexed Detection (Adv. Funct. Mater. 4/2018). (22nd January 2018) - Park, Youngrong; Ryu, Yeon‐Mi; Wang, Taejun; Jung, Yebin; Kim, Sohee; Hwang, Sekyu; Park, Joonhyuck; Bae, Dong‐Jun; Kim, Jaeil; Moon, Heejo; Lim, Hyun‐Suk; Kim, Sang‐Yeob; et al.
Abstract : Two imaging probes can be co‐used for colonoscopic diagnosis: a fluorescent probe that ratiometrically switches between two colors in response to λ‐glutamyltranspeptidase activity and an antibodyquantum dot probe. As shown by Ki Hean Kim, Sungjee Kim, Seung‐Jae Myung, and co‐workers in article number1703450, co‐application of two probes affords accurate visualization of early‐stage carcinomas that are not easily discernible with the naked eye.